Secondary School Students’ Contact Experiences and Dispositions towards English as an International Language – A Pilot Study - Illés, Éva; Csizér, Kata (Working Papers in Language Pedagogy, 2010)
The objective of this small-scale study is twofold. On the one hand, it investigates the contact experiences and the attitude of secondary school students towards English as an international language. On the other, it offers an insight into the validation of a questionnaire by foregrounding the process where a pilot questionnaire has been evaluated and amendments have been suggested. The research is based on a sample comprising 50 secondary school students living in Budapest. The main finding of this study is that an awareness of the role of English in international contexts of communication does not result in increased openness towards various varieties of English and the search for contact opportunities on the part of the learners. The results of the study also indicate that the notion of English as an international language as a simplified language and its subsequent demotivating influence seem to diminish the amount of effort learners are prepared to devote to the learning of English outside the classroom.